Interprovincial migration in China: the effects of investment and migrant networks - Shuming Bao; Örn B. Bodvarsson; Jack W. Hou; Yaohui Zhao (Institute for the Study of Labor (IZA), 2007)
Since the 1980s, China's government has eased restrictions on internal migration. This easing, along with rapid growth of the Chinese economy and substantial increases in foreign and domestic investments, has greatly stimulated internal migration. Earlier studies have established that migration patterns were responsive to spatial differences in labor markets in China, especially during the 1990s. However, other important economic and socio-political determinants of interprovincial migration flows have not been considered. These include the size of the migrant community in the destination, foreign direct and domestic fixed asset investments, industry and ethnic mixes and geographic biases in migration patterns. We estimate a modified gravity model of interprovincial migration in China that includes as explanatory variables: migrant networks in the destination province, provincial economic conditions, provincial human capital endowments, domestic and foreign investments made in the province, industry and ethnic mixes in the province, provincial amenities and regional controls, using province-level data obtained from the National Census and China Statistical Press for the 1980s and 1990s. We find strong evidence that migration rates rise with the size of the destination province's migrant community. Foreign and domestic investments influence migration patterns, but sometimes in unexpected ways. We find that as economic reforms in China deepened in the 1990s, the structure of internal migration did not change as much as earlier studies have suggested. Consequently, our results raise new questions about the World's largest-scale test case of internal migration and strongly suggest a need for further research.
Keywords: 330; Binnenwanderung; Regionale Arbeitsmobilität; Soziales Netzwerk; Region; Investition; Direktinvestition; China